Experimental validation of a computational fluid dynamics model using micro‐particle image velocimetry of the irrigation flow in confluent canals - Pereira, Mário (2022)
This study aimed to experimentally validate a computational fluid dynamics (CFD) model, using micro-particle image velocimetry (micro-PIV) measurements of the irrigation flow velocity field developed in confluent canals during irrigation with a side-vented needle. A microchip with confluent canals, manufactured in polydimethylsiloxane was used in a micro-PIV analysis of the irrigation flow using a side-vented needle placed 3 mm from the end of the confluence of the canals. Velocity fields and profiles were recorded for flow rates of 0.017 and 0.1 ml/s and compared with those predicted in CFD numerical simulations (using a finite volume commercial code – FLUENT) for both laminar and turbulent regimes. The overall flow pattern, isovelocity and vector maps as well as velocity profiles showed a close agreement between the micro-PIV experimental and CFD predicted data. No relevant differences were observed between the results obtained with the laminar and turbulent flow models used. Results showed that the laminar CFD modelling is reliable to predict the flow in similar domains.